Unlocking the World of Words: Exploring the Use of Picture Storybooks in Enhancing Early Childhood Speaking Skills - Kusumawati (Journal of Early Childhood Education Research, 2025)
Purpose: Speaking ability is a fundamental aspect of early childhood language development, as it underpins effective communication and social interaction. However, many children in early childhood education settings still exhibit limited speaking skills, necessitating appropriate instructional strategies. This study aims to describe teacher strategies in improving early childhood speaking skills through picture storybooks and to identify the supporting and inhibiting factors in the learning process at Group B of TK Islam Yaroja. Methodology: This study employed a descriptive qualitative approach. The participants consisted of one classroom teacher and 20 children of Group B at TK Islam Yaroja. Data were collected through observation, interviews, and documentation. The data were analyzed using an interactive model comprising data reduction, data display, and conclusion drawing to ensure the credibility and trustworthiness of the findings. Results : The findings revealed that teacher strategies, including interactive reading, question-and-answer activities, and story retelling using picture storybooks, effectively improved children's speaking skills. Of the twelve children who were initially categorized as undeveloped, ten showed significant improvement, progressing into the developing and developed as expected categories. Supporting factors included children's enthusiasm toward picture storybooks and the teacher's creativity in delivering stories, while inhibiting factors included limited book availability and varying levels of children's confidence. Conclusions: Picture storybooks serve as an effective learning medium for stimulating children's confidence and enhancing their speaking ability in early childhood education settings. Teacher strategies that incorporate interactive and dialogic approaches through picture storybooks can significantly foster children's verbal development. These findings contribute to the growing body of literature on early childhood language pedagogy and offer practical implications for educators seeking to optimize speaking skill development in kindergarten settings.